Explication of the “Book” concept in lexicographic representation - Filimonova, A.P.; Mazhitaeva, Sh.M.; Kozlovskaya, N.V.; Rapisheva, Zh.D. (KU Publ., 2021)
One of the topical issues of modern linguoconceptology is studying the specifics of concepts functioning in various discourses, such as political, economic, medical, artistic, etc. Such a study is based on the preliminary construction of the most characteristically complete model of the concept that serves as “an intra-linguistic standard of comparison” (Vorkachev). It serves as a basic semantic prototype reflecting the main definitional semes of the concept under consideration against the background of which the discursively conditioned specifics can be identified. In this article, the concept “book” is described as a significant element of the national language world image. Based on the analysis of lexicographic data and the main frame propositions, a semantic model of the concept is structured, the complex of its representatives in the Russian language is determined.
«Кітап» концептісінің лексикографикалық мағынадағы сипаттамасы
Экспликация концепта «книга» в лексикографическом отражении
Keywords: linguocultural concept; frame structures; ‘book’ concept; lexicographic representation